A Comparison of the Time Spent in Emergency Departments by Older Adults With and Without Mental Health Needs. (April 2021) - Goode, Deborah; Slater, Paul; Ryan, Assumpta; Melby, Vidar
Abstract : Older adults present to emergency medical services with a multitude of clinical and functional needs due to polypharmacy and multipathology. Older adults with mental health needs require additional time for the more comprehensive assessment required as a result of their underlying mental health condition. This article compares the time spent in emergency departments by older adults who have a mental health need with those who do not. Information on how they access prehospital and inhospital care is examined alongside key factors that impact on time spent in emergency departments. Data were collected from hospital records of older adults presenting at emergency departments in 3 large Health and Social Care Trusts in the United Kingdom using a retrospective, secondary, official personal information database source over 1 year. A total sample of 74, 766 attendance records of older adults older than 65 years were examined. adults who presented with or had a mental health condition in their diagnosis or history, which made up a subsample of 1, 818 people, were found to have significant differences in the time spent in emergency departments and some notable differences in trends and admission patterns. They wait longer than the older person without mental health needs, are more likely to breach the 4-hr waiting time target, are admitted in higher numbers, and rely heavily on the ambulance service. Health and social care systems and services need to undergo transformations to ensure that all people who access services are treated fairly and effectively.